How Informational Constraints for Decision-Making on Passing, Dribbling and Shooting Change With the Manipulation of Small-Sided Games Changes in Futsal. Issue 4 (August 2021) - Pizarro, David; Práxedes, Alba; Travassos, Bruno; Gonçalves, Bruno; Moreno, Alberto
In this study, we explored how manipulating floaters' positions in small-sided futsal games (SSGs) promote changes in the informational constraints that support decision-making (DM) for passing, dribbling and shooting tactics. We made changes in four experimental 3 vs 3 small-sided game conditions with 30 male futsal players (U19 age category): (a) Floaters Off (FO), (b) Final Line Floaters (FLF), (c) Lateral Floaters own field sideline (LFofsl) and (d) Lateral Floaters full field sideline (LFffsl). We assessed players' activity with WIMU PRO™ software during the SSGs, using the Game Performance Evaluation Tool (GPET) to analyze a total of 1, 635 decisions. DM for dribbling was generally based on the interpersonal distance between the ball carrier and direct opponent, considering the defensive team length and the offensive team area. Shooting decisions were constrained, by certain attacking-defending teams' spatial-temporal relations with regard to playing space and team balance as affected by manipulating floaters' positions. The coaches' decisions to change the floaters' positions during SSGs may change informational variables sustaining the dribbling decision, but no changes in SSG variables affected passing DM.